2014
DOI: 10.1016/j.prostaglandins.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Arg287Gln variant of EPHX2 and epoxyeicosatrienoic acids are associated with insulin sensitivity in humans

Abstract: Epoxyeicosatrienoic acids (EETs) protect against the development of insulin resistance in rodents. EETs are hydrolyzed to less biologically active diols by soluble epoxide hydrolase (encoded for by EPHX2). Functional variants of EPHX2 encode for enzymes with increased (Lys55Arg) or decreased (Arg287Gln) hydrolase activity. This study tested the hypothesis that variants of EPHX2 are associated with insulin sensitivity or secretion in humans. Subjects participating in metabolic phenotyping studies were genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Furthermore, these data are consistent with a previously reported inverse association between circulating EET and monocyte chemoattractant A few additional studies have quantifi ed plasma EET levels in patients at risk for or with established cardiovascular disease. Ramirez et al ( 38 ) found that presence of the metabolic syndrome was associated with lower circulating EET levels. Furthermore, Minuz et al ( 39 ) reported that patients with renovascular disease had lower circulating EETs compared with both healthy volunteer and essential hypertension controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these data are consistent with a previously reported inverse association between circulating EET and monocyte chemoattractant A few additional studies have quantifi ed plasma EET levels in patients at risk for or with established cardiovascular disease. Ramirez et al ( 38 ) found that presence of the metabolic syndrome was associated with lower circulating EET levels. Furthermore, Minuz et al ( 39 ) reported that patients with renovascular disease had lower circulating EETs compared with both healthy volunteer and essential hypertension controls.…”
Section: Discussionmentioning
confidence: 99%
“…[34] We have found that plasma EET concentrations are lower in individuals with the metabolic syndrome than in those without the metabolic syndrome (Figure 2). [35] Similarly, EET concentrations correlate with insulin sensitivity in individuals assessed during hyperglycemic clamps (Figure 3). …”
Section: The Eet Pathway and Insulin Sensitivity In Humansmentioning
confidence: 92%
“…[38] We have observed an association between the loss-of-function EPHX2 287Gln variant and increased insulin sensitivity. [35] Interestingly, the relationship between the EPHX2 287Gln variant and insulin sensitivity varied with body mass index (BMI), such that at an overweight BMI of 25 kg/M 2 , insulin sensitivity was 180% higher (95% CI: 45–439%, p=0.002) in EPHX2 287Gln carriers compared to Arg/Arg homozygotes, whereas at an obese BMI of 30 kg/M 2 insulin sensitivity was 40% higher (95% CI: 0–130%, p=0.05) in carriers of the EPHX2 287Gln, and at higher BMI there was no relationship between insulin sensitivity and genotype (Figure 4). These data suggest that decreasing sEH activity in patients at risk for T2DM could enhance insulin sensitivity.…”
Section: The Eet Pathway and Insulin Sensitivity In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the lead candidate genes identified in an earlier genome-wide association study [21], the use of an exon sequencing approach [14] coupled with rigorous association and replication analyses of 152 candidate genes led to the identification of soluble epoxide hydrolase 2 ( EPHX2 ) as a novel AN gene [14]. EPHX2 is a gene known to be associated with subclinical cardiovascular disease [22, 23], stroke [24], insulin resistance [25], cholesterol phenotypes [26], and kidney functions [27]. The surprising discovery of its association to a major psychiatric illness opens up the possibility that researchers have been choosing an incomplete set of “candidate genes” due to insufficient understanding of genes’ biology.…”
Section: Introductionmentioning
confidence: 99%